Effect of drill speed during drilling of human cadaveric tibiae - Fernandes, M.G.A. (2018)
Boné fracture is a feature ofeveryday life. Most of the treatments involve boné drilling to fixation of implanted medicai devices. Boné loss due to excessive produced heat during drilling may weaken lhe purchase of surgically placed scre-ws and pins, causing them to loosen postoperatively. Decrease the heat generation hás a great demand as it helps in better fixation and healing of boné tissue. This paper presents an experimental model to study the effect of drill speed using human cadaveric tibiae.